Decoherence suppression in quantum systems 2008 - Nakahara, Mikio; Rahimi, Robabeh; SaiToh, Akira (World Scientific Pub. Co., 2010)
This volume provides an overview on the decoherence suppression methods in quantum computing, open quantum systems, quantum error correction and fault-tolerant quantum computing. It also includes concepts in geometric quantum computing by composite pulses. Quantum wipe effect is explained as an approach for suppressing decoherence of the system. A short contribution on the implementation of holonomic quantum gates with NMR (Nuclear Magnetic Resonance) is presented. The lecture notes contributed to this volume are prepared in a self-contained manner hence readers with limited knowledge on the topics could understand the discussions by following the sequence of chapters which begin with mathematical frameworks and progress to the most updated outcomes of the fields. The volume will be useful for a broad audience from graduate students to researchers interested in the field.
Keywords: Quantum theory -- Congresses.; Théorie quantique -- Congrès.; SCIENCE -- Physics -- Quantum Theory.; Quantum theory; Electronic book.; Conference papers and proceedings